2007
DOI: 10.1093/nar/gkm417
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for recognition of cognate tRNA by tyrosyl-tRNA synthetase from three kingdoms

Abstract: The specific aminoacylation of tRNA by tyrosyl-tRNA synthetases (TyrRSs) relies on the identity determinants in the cognate tRNATyrs. We have determined the crystal structure of Saccharomyces cerevisiae TyrRS (SceTyrRS) complexed with a Tyr-AMP analog and the native tRNATyr(GΨA). Structural information for TyrRS–tRNATyr complexes is now full-line for three kingdoms. Because the archaeal/eukaryotic TyrRSs–tRNATyrs pairs do not cross-react with their bacterial counterparts, the recognition modes of the identity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 54 publications
2
62
0
Order By: Relevance
“…For tRNAs His , it was experimentally shown (see Table 3) that Aeropyrum pernix K1 uses position N73 (Nagatoyo et al 2005). Regarding tRNAs Tyr , it was found that three positions (other than the anticodon) are assumed to participate in the recognition process: N72, N1, and N73 (Fechter et al 2001;Iwaki et al 2002Iwaki et al , 2012Tsunoda et al 2007). This is in agreement with our results where positions N72 and N1 are found to be highly informative (both contain nearly the same information due to their Watson-Crick bonds).…”
Section: Different Species Have a Unique Ensemble Of Codes In The Infsupporting
confidence: 91%
See 1 more Smart Citation
“…For tRNAs His , it was experimentally shown (see Table 3) that Aeropyrum pernix K1 uses position N73 (Nagatoyo et al 2005). Regarding tRNAs Tyr , it was found that three positions (other than the anticodon) are assumed to participate in the recognition process: N72, N1, and N73 (Fechter et al 2001;Iwaki et al 2002Iwaki et al , 2012Tsunoda et al 2007). This is in agreement with our results where positions N72 and N1 are found to be highly informative (both contain nearly the same information due to their Watson-Crick bonds).…”
Section: Different Species Have a Unique Ensemble Of Codes In The Infsupporting
confidence: 91%
“…For example, published work on the role of the paired positions N2:N71 in tRNAs for the aminoacylation of tyrosine shows that while bacteria's aaRS requires the G:C nucleotides pair in these positions for proper aminoacylation, such a structure does not enable the aminoacylation of tyrosine in humans or Archaea. Yet the simple switch to C:G in N2:N71, in the tRNA, does enable this species-specific aminoacylation (Quinn et al 1995;Wakasugi et al 1998;Tsunoda et al 2007). In our study, we found that Archaea species contain the relevant information in positions N1:N72, and not N2:N71 (as it was also found experimentally, see Table 3.).…”
Section: Discussionmentioning
confidence: 99%
“…Rv2275 reportedly forms a dimer, similar to the class Ic aaRSs, which must dimerize for tRNA binding (with the tRNA bound across both monomers) (15) (Fig. S5).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of mt-tRNA Tyr , a direct implication of G15 and A22 in the tyrosylation process is ruled out based on crystallographic knowledge of the mt-TyrRS (Bonnefond et al 2007b) and of T. thermophilus (Yaremchuk et al 2002), Methanococcus jannaschii (Kobayashi et al 2003), and cytosolic Saccharomyces cerevisiae (Tsunoda et al 2007) tRNA Tyr /TyrRS complexes. We show here that the aminoacylation deficiencies are due to structural perturbations and correspond to the initial impact of the mutations.…”
Section: Final Considerationsmentioning
confidence: 99%